KEBIJAKAN HUKUM PIDANA DALAM PENYELESAIAN TINDAK PIDANA RINGAN YANG DILAKUKAN OLEH LANSIA MELALUI PENDEKATAN RESTORATIVE JUSTICE - Ramadatul Fajri; Davit Rahmadan; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Nowadays, the perpetrators of criminal offense come from various circles,one of which is carried out by people who are elderly, according to existingregulations, the elderly are included in the vulnerable category which is entitledto more treatment and protection with respect to their specificity, but in practicein positive law In Indonesia, there are no rules governing the protection of theelderly who are in conflict with the law, before the law the elderly are stillequalized with perpetrators of criminal offense of productive age. In theimplementation of law enforcement against perpetrators of criminal offense of theelderly, it is still necessary to review the problem of law enforcement and effortsto resolve criminal offense, restorative justice in terms of acting as a media thatbridges the settlement of criminal offense by approaching or mediating betweenperpetrators and victims.The purpose of this study are: first, to determine legal policy towards theelderly, second, to determine the arrangements for efforts to resolve criminal actsby the elderly through a restorative justice approach. This type of research can beclassified as normative research or better known as